Penicilloyl-Polylysine Stability and Clinical Use Over Time - Macy, Eric (The Permanente Journal, 2007)
Background: The major penicillin skin test reagent, penicilloyl-polylysine, has not been commercially available since October 2004. The minimal concentration of penicilloyl-polylysine necessary for safe penicillin skin testing has not been determined. Methods: Penicillin skin testing was performed on 596 individuals between October 2004 and October 2006 using out-of-date commercially produced penicilloyl-polylysine as part of a complete panel of reagents. The concentration of active penicilloyl-polylysine was measured. Outcomes were compared with those for 921 individuals tested between October 2002 and September 2004 using in-date commercially produced penicilloyl-polylysine. Results: There was no significant difference in the fraction of patients who had positive skin test results using indate (5.1%) versus out-of-date (4.7%) penicilloyl-polylysine. There were four mild but no serious adverse reactions in the patients tested with the outdated reagent who were then challenged with oral penicillin class antibiotics. Conclusion: Penicillin skin testing can be safely done using penicilloyl-polylysine down to a concentration of 4.29 × 10(−5) M.